Japanese private international law - Nishioka, Kazuaki; Nishitani, Yuko (London, England : Zed Books, 2021)
"This is the leading reference on Japanese private international law in English. The chapters systematically cover the whole of Japanese private international law, not just questions likely to arise in commercial matters, but also in family, succession, cross-border insolvency, intellectual property, competition (antitrust), and environmental disputes. The chapters do not merely cover the traditional conflict of law areas of jurisdiction, applicable law (choice of law), and enforcement. The chapters also look into conflict of law questions arising in arbitration and assess Japanese involvement in the global harmonisation of private international law. In addition to summarising relevant principles and scholarly views, the authors discuss case law whenever possible and identify deficiencies and anticipate difficulties in the existing law. The book thus presents the Japanese conflict of laws through a combination of common and civil law analytical techniques and perspectives, providing readers worldwide with a more profound and comprehensive understanding of the subject."--
Table of Abbreviations -- Table of Cases -- 1. Introduction 1. The Subject Matter of Private International Law 2. Sources of Private International Law 3. History of Private International Law in Japan 4. Preliminary Matters 5. Connecting Factors 6. Substance and Procedure 7. Proof, Ascertainment and Application of Foreign Law 8. Mandatory Rules, Ordre Public , Escape Clauses and Evasion of Law -- 2. Jurisdiction 1. General Principles 2. Civil and Commercial Matters -- 3. Status and Family Matters -- 4. Other Matters 5. Immunities from Jurisdiction -- 3. Choice of Law 1. Persons 2. Law of Obligations 3. Law of Property 4. Intellectual Property -- 5. Family and Succession Law 6. Insolvency Law 7. Competition Law -- 4. Recognition and Enforcement of Foreign Judgments 1. Recognition 2. Enforcement of Judgments 3. Recognition of Foreign Insolvency Proceedings -- 5. Arbitration and Mediation 1. International Commercial Arbitration 2. Investment Arbitration 3. Mediation -- 6. The Harmonisation of Private International Law 1. Japan's Role in the Work of the Hague Conference, UNCITRAL, UNIDROIT and Other Organisations 2. The Future of Private International Law -- Glossary -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web
Keywords: Conflict of laws -- Japan; Commercial law -- Japan; Investments, Foreign -- Law and legislation -- Japan; Private international law & conflict of laws,Commercial law,Japan; Electronic books